Social support and optimism as protective factors for mental health among 7765 healthcare workers in germany during the COVID-19 pandemic: Results of the voice study - Schug, Caterina; Morawa, Eva; Geiser, Franziska; Hiebel, Nina; Beschoner, Petra; Jerg-Bretzke, Lucia; Albus, Christian; Weidner, Kerstin; Steudte-Schmiedgen, Susann; Borho, Andrea; Lieb, Marietta; Erim, Yesim (International Journal of Environmental Research and Public Health, 2021)
Background: The COVID-19 pandemic is impacting mental health worldwide, particu-larly among healthcare workers (HCWs). Risk and protective factors for depression and generalized anxiety in healthcare workers need to be identified to protect their health and ability to work. Social support and optimism are known protective psychosocial resources, but have not been adequately studied in the context of the COVID-19 pandemic among healthcare workers in Germany. Methods: Within the first wave of the VOICE study (n = 7765), a longitudinal web-based survey study among healthcare workers in Germany, we assessed symptoms of depression (PHQ-2) and generalized anxiety (GAD-2), social support (ENRICHD Social Support Inventory; ESSI), and generalized optimism as well as sociodemographic, occupational, and COVID-19 related variables. Multiple linear regression analyses were conducted to examine associations between the constructs. Results: The analyses revealed that higher levels of social support and optimism were associated with lower levels of depression and generalized anxiety. They showed a higher association with depression and generalized anxiety than demographic or occupational risk factors such as female gender and direct contact with infected individuals. Conclusion: Psychosocial resources such as social support and optimism appear to contribute to successful coping with the COVID-19 pandemic and should be considered in future studies.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Anxiety; COVID-19; Depression; Healthcare; Mental health; Optimism; Resources; Social support